Levinas and the paths of Philosophy - Tahim, Demetrius Oliveira (Argumentos - Revista de Filosofia, 2010)
To Emmanuel Levinas (1906 – 1995), philosophy, as well as sciences, may be represented by the pursuit of truth; however it’s a wild representation and empty at first. Such pursuit may take two paths: the first is the one the truth is closely attended with experience. Who thinks keeps, in truth, a relationship with what is dif- ferent from him. Truth involves relationship with exteriority, with transcendence and with the other. However, truth means a free investigation on the part of the thinker, who does not find any limitations of inquiring. Such truth is the practice of denying the other itself, not been alienated in its own movement, for the contact with the other’s reality does not prevent its progress. From this, the pursuit of truth, as a practice of freedom, may be understood as a walk of the autonomy, its own walk. Philosophy could not be other than that walk of appropriation of existence by the man, along the history. Said that, the purpose of this work is to discourse about the choice the philosophy made, it is, lost most part of its journey in benefit of the defense of liberty and, consequently, of itself, proclaiming the anteriority of autonomy to the detriment of heteronomy: “violence” and appropriation would be explained.